Merunut Makna Kata â€œRefreshingâ€ dan â€œHealingâ€: Kajian Sosiolinguistik - Viktorius P. Feka; Selfiana T. M. Ndapa Lawa; Darius Y. Nama (FKIP Universitas Citra Bangsa, 2023)
This article aims to explain the differences in meanings between the words